2015
DOI: 10.1017/s1368980015001937
|View full text |Cite
|
Sign up to set email alerts
|

WHO European Childhood Obesity Surveillance Initiative: health-risk behaviours on nutrition and physical activity in 6–9-year-old schoolchildren

Abstract: Objective: To assess to what extent eight behavioural health risks related to breakfast and food consumption and five behavioural health risks related to physical activity, screen time and sleep duration are present among schoolchildren, and to examine whether health-risk behaviours are associated with obesity. Design: Cross-sectional design as part of the WHO European Childhood Obesity Surveillance Initiative (school year 2007/2008). Children's behavioural data were reported by their parents and children's we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
76
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 39 publications
7
76
1
5
Order By: Relevance
“…Other studies have evaluated the influence of energy-related behaviors (including data on diet or some food group’s intake or breakfast consumption, physical activity, sedentary time and sleep duration) and obesity in children and adolescents [15–17, 34, 35]. The studies by Duncan et al [34] and Danielzik et al [35] were the first ones that examined the cumulative effects of multiple risk factors on adiposity in children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have evaluated the influence of energy-related behaviors (including data on diet or some food group’s intake or breakfast consumption, physical activity, sedentary time and sleep duration) and obesity in children and adolescents [15–17, 34, 35]. The studies by Duncan et al [34] and Danielzik et al [35] were the first ones that examined the cumulative effects of multiple risk factors on adiposity in children.…”
Section: Discussionmentioning
confidence: 99%
“…The studies by Duncan et al [34] and Danielzik et al [35] were the first ones that examined the cumulative effects of multiple risk factors on adiposity in children. Except for the study by Duncan et al that was conducted in New Zealand [34], all of them were conducted in European countries, either analyzing selected samples [35], national samples [15] or multi-country data [16, 17]. Pérez-Rodrigo et al [15] identified a combination of high physical activity level, low sedentary time and longer sleep time to be associated with a lower prevalence of obesity in a representative sample of Spanish children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This report identified indicators that assess not only outcomes such as obesity, diet, and physical activity, but also a variety of environmental and policy measures, including political will, cultural climate, dietary and activity norms, and legislative efforts. Environmental measures are being incorporated into existing surveillance systems, such as the COSI protocol, which includes detailed school environmental measures as an option (112,113).…”
Section: Environmental-level Datamentioning
confidence: 99%
“…Esta tendencia deberá confirmarse con posteriores recogidas de información en años venideros. Estos datos pueden compararse con los datos a nivel europeo, de estudios similares al estudio Aladino (29,30).…”
Section: Estado Actual De La Cuestión Obesidad Infantil Y Juvenil En unclassified